KAJIAN DAMPAK POLA MASSA BANGUNAN TERHADAP IKLIM MIKRO DI AREA PERMUKIMAN - Christian Nindyaputra Octarino (RUSTIC, 2022)
In recent years, climate change has become a global phenomenon faced all over the world. This situation potentially has a significant impact on the quality of the environment and the resident’s quality of life. Discussing the environmental quality cannot be separated from the settlement area, which is the place for people’s daily lives. The quality of a settlement area is one of the factors that determine the quality of human life. Especially after experiencing a pandemic period for more than 2 years, the need for a comfortable and healthy living environment is increasing. One of the environmental comfort levels can be observed from the quality of the microclimate. A good microclimate will play a role in maintaining the health of residents and also the quality of the environment to prevent climate change. This study aims to identify a correlation between the physical elements of settlement and the quality of microclimate. The study was conducted in two settlement areas, namely Baciro and Suryatmajan, located in the city of Yogyakarta. These two areas have different characteristics in terms of settlement patterns, which is one of the factors that influence the microclimate. The method used is direct observation and field measurement for the data related to the microclimate and physical elements in the settlement area. The results show that each physical element of the settlement will affect each other in terms of creating the quality of microclimate, so it cannot be relying on just one variable. This result can be used as an essential consideration to propose design strategies for a healthy, comfortable, and sustainable human settlement.